Efficiency of shower and sprinkler irrigation system on curly red chili in coastal area Kulon Progo, Indonesia, using a stochastic frontier approach - FRANCY RISVANSUNA FIVINTARI; NURMALITA NURMALITA; JAZAUL IKHSAN; MULYONO MULYONO; FRANCY IRIANI EKAWATI; YUNANTO YUNANTO; RISKA AULA ARDILA (Asian Journal of Agriculture, 2026)
Abstract. Fivintari FR, Nurmalita, Ikhsan J, Mulyono, Ekawati FI, Yunanto, Ardila RA. 2026. Efficiency of shower and sprinkler irrigation system on curly red chili in coastal area Kulon Progo, Indonesia, using a stochastic frontier approach. Asian J Agric 10 (1): g100161. https://doi.org/10.13057/asianjagric/g100161. Coastal agriculture faces significant production challenges due to sandy soil characteristics, limited water retention, and increasing pressure on water resources. Improving irrigation efficiency is therefore essential to enhance productivity and sustainability in these environments. This study aims to evaluate the technical efficiency of curly red chili production under shower and sprinkler irrigation systems in the coastal area of Kulon Progo, Indonesia. The analysis employs a Cobb–Douglas production function estimated using the Stochastic Frontier Analysis (SFA) approach, which allows for the separation of random shocks and technical inefficiency in agricultural production. Both irrigation groups were technically efficient, with average technical efficiency levels above 0.7. However, sprinkler irrigation was more efficient than shower irrigation, with average scores of 0.902 and 0.795, respectively. Overall, the curly red chili farming business can achieve a maximum production of around 82.2% by using a combination of various production factors, suggesting that output could still be increased by approximately 17.8% through better input management and technology adoption without expanding resource use. The findings further demonstrate that irrigation technology plays a critical role in determining production efficiency. In particular, sprinkler irrigation is found to be more technically efficient than shower irrigation, reflecting its advantages in water distribution and labor use in sandy coastal conditions. These results highlight the importance of appropriate irrigation system selection as a key strategy for improving farm performance in coastal agriculture. The study provides empirical evidence to support the promotion of more efficient irrigation technologies and targeted extension programs aimed at enhancing technical efficiency. Overall, the findings contribute to the literature on irrigation efficiency in coastal farming systems and offer practical insights for farmers and policymakers seeking to improve productivity under challenging environmental conditions.